Assessment of right atrial and right ventricular size in children after percutaneous closure of secundum atrial septal defect with Amplatzer septal occluder - Kucinska, Beata (Termedia Publishing House, 2010)
INTRODUCTION: The aim of this study was to evaluate the right atrial (RA) and right ventricular (RV) size, and the speed of their normalization, in children after percutaneous closure of secundum atrial septal defect with the Amplatzer septal occluder. MATERIAL AND METHODS: The study group consisted of 42 children, aged 4.5 to 18.5 years. The following measurements (indexed to body surface area) were performed using 2D echocardiography: longitudinal, transverse axis and area of RA, RV inflow dimensions at one-third, and halfway between the tricuspid annulus and the apex (in the apical 4-chamber view), short axis and M-mode RV diastolic dimensions. All measurements were obtained 24 h and 1, 3 and 12 months after the procedure, then annually over 4 years of follow-up, and compared with the values obtained from the control groups. RESULTS: A significant decrease in all RA and RV values was observed after 24 h. Right ventricular transverse dimension normalized after 1 month, the RA longitudinal axis and area and the RV inflow dimensions after 3 months, and the RA transverse axis and M-mode RV diastolic dimension after 2 years, but the ratio of transverse to longitudinal RA axis remained significantly higher. CONCLUSIONS: Right atrial and right ventricular measurements decrease rapidly during the first 24 h, and most of them normalize within a 3-month period. M-mode RV diastolic dimension does not capture the real RV changes. Amplatzer septal occluder closure of ASD influences the RA geometry, which is reflected by the higher transverse to longitudinal RA axis ratio.